USING WEBSITE AS A TOOL FOR PRACTICING ENGLISH LISTENING SKILL - Desi Surayatika (Universitas Indo Global Mandiri, 2017)
Listening is a process included activity of listening sound of language and visual aspect, identify, interprete, value, and do reaction for the content of meaning. Technology is useful to teach listening because each type of technology provides opportunities for students to explore their ranges of listening strategies.Multimedia technology becomes more accessible to teachers and learners of other languages, its potential as a tool to enhance listening skills becomes a practical option. The technology mediates the process, getting language out there and giving feedback that shows whether someone has or hasn’t understood what people have said.It makes that possible wherever people are in the world. Teachers and learners can go online to listen to material about different areas of interest, and can then speak about what they have discovered, telling others in the class or other classes elsewhere in the world. The Internet is suitable place to practice languages as it offers the possibility, with the right software, of using images and audio resources at the same time, combining sounds and images as in communicative situations in the real world. It also provides users with a highly appealing and innovative format. But only when the sources are properly selected can the internet be useful in learning environment. There is a plethora of educational material available online and accessible via Web search engines. In short, using websites for practicing listening can be a good assistance for students to practice their language learning ability.Key words: Listening, English, Website